Functional Characterization of the Nep1-Like Protein Effectors of the Necrotrophic Pathogen – Alternaria brassicae - Duhan, Deepak; Gajbhiye, Shivani; Jaswal, Rajdeep; Singh, Ravindra Pal; Sharma, Tilak Raj; Rajarammohan, Sivasubramanian (Frontiers in Microbiology, 2021)
Alternaria brassicae is an important necrotrophic pathogen that infects the Brassicaceae family. A. brassicae, like other necrotrophs also secretes various proteinaceous effectors and metabolites that cause cell death to establish itself in the host. However, there has been no systematic study of A. brassicae effectors and their roles in pathogenesis. The availability of the genome sequence of A. brassicae has enabled the search for effectors and their functional characterisation. Nep1-like proteins are a superfamily of proteins that induce necrosis and ethylene biosynthesis. They have been reported from a variety of microbes including bacteria, fungi, and oomycetes. In this study, we identified two NLPs from A. brassicae viz. AbrNLP1 and AbrNLP2 and functionally characterised them. Although both AbrNLPs were found to be secretory in nature, they localised differentially inside the plant. AbrNLP2 was found to induce necrosis in both host and nonhost species, while AbrNLP1 could not induce necrosis in both species. Additionally, AbrNLP2 was shown to induce pathogen-associated molecular pattern (PAMP)-triggered immunity in both host and nonhost species. Overall, our study indicates that AbrNLPs are functionally and spatially (subcellular location) distinct and may play different but important roles during the pathogenesis of A. brassicae.